Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2000
DOI: 10.1145/332040.332477
|View full text |Cite
|
Sign up to set email alerts
|

The social life of small graphical chat spaces

Abstract: This paper provides a unique quantitative analysis of the social dynamics of three chat rooms in the Microsoft V-Chat graphical chat system. Survey and behavioral data were used to study user experience and activity. 150 V-Chat participants completed a web-based survey, and data logs were collected from three V-Chat rooms over the course of 119 days. This data illustrates the usage patterns of graphical chat systems, and highlights the ways physical proxemics are translated into social interactions in online e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 4 publications
2
26
0
Order By: Relevance
“…These statements imply that people perceive physical touch differently than a visual representation of touch, even if that visual representation is dynamic and realistic, contrary to some VR work (e.g., [12,21,22]). The touch avoidance first seen in the physical-table study appears to be dependent on a true sensation of touch rather than a visual representation.…”
Section: Differences Between Physical and Digital Embodimentsmentioning
confidence: 95%
See 1 more Smart Citation
“…These statements imply that people perceive physical touch differently than a visual representation of touch, even if that visual representation is dynamic and realistic, contrary to some VR work (e.g., [12,21,22]). The touch avoidance first seen in the physical-table study appears to be dependent on a true sensation of touch rather than a visual representation.…”
Section: Differences Between Physical and Digital Embodimentsmentioning
confidence: 95%
“…People also assign personal space to avatars. For example, research has found that people treat their avatar's personal space as they would their own [12], that they are uncomfortable with invasions of their avatar's personal space (e.g., [12,21,22]), and that they use gaze avoidance to compensate for these invasions [31]. In addition, people avoid actions that could cause others to be uncomfortable (e.g., walking though another's avatar) [21].…”
Section: Personal Space In Digital Environmentsmentioning
confidence: 99%
“…Smith et al have added a substantial cache of methods and perspectives by studying the interaction and structure of Usenet (Smith 1999;Turner et al 2006). Usenet is an online bulletin board-type system commonly called newsgroups, although they are not necessarily associated with news, as many ''newsgroups'' are for recreational, technical, political, and cultural topics.…”
Section: Social Network Analysis In Virtual Environmentsmentioning
confidence: 99%
“…Studies on emoticons and avatars report positive effects on computer-mediated communication. These studies indicate that emoticons and avatars improve user experiences and interactions among participants (Damer 1997;Smith et al 2000;Pesson 2003) and build enthusiasm toward participation and friendliness in intercultural communication (Koda 2004;Isbister et al 2000).…”
Section: Introductionmentioning
confidence: 99%